(untitled) (Faridpur Medical College Journal, 2021)
Seborrheic dermatitis is a common chronic disease. Malassezia yeasts have been implicated in the pathogenesis of this disease. Antifungal agents are known to be effective in the treatment of Malassezia yeast infections. This study was done to evaluate the efficacy of itraconazole in the treatment of seborrheic dermatitis. Sixty patients with Seborrheic dermatitis were evaluated in an open non-comparative study. Patients were treated with itraconazole capsule 100 mg twice a day for a week; then after a 3-week interval 100 mg capsule was given twice a day for 2 days of following months for two consecutive months. Four clinical parameters (Itching, burning erythema, scaling, and seborrhea) were assessed using a 0 to 3-point (0= absent, 1 = mild, 2 = moderate, 3 = severe) score. Mycological evaluation determined the presence of Malassezia spores in the scales using a direct smear. At the end of the initial treatment significant improvement was reported in four clinical parameters: Itching, burning erythema, scaling, and seborrhea. Maintenance therapy led to further improvement slightly. Burning sensation mildly improved during the treatment. The quantity of Malassezia spores present in the direct smear decreased throughout the treatment period. Blood test abnormalities were not found during the treatment. So initial treatment with itraconazole is beneficial in patients with seborrheic dermatitis. Faridpur Med. Coll. J. 2021;16(1):21-24